National Renewal and Strategic Change -First lessons from an Early-Mover in Deregulation - Campbell-Hunt, Colin; Harper, David; Hamilton, Robert (School of Management Working Papers, 1993)
The scope and pace of economic liberalisation in New Zealand have been judged by the OECD as the most extensive of any undertaken in a developed economy during the past decade. This paper reports on a project aimed at determining how and at what rate New Zealand businesses have adapted to this major deregulation of their commercial environment. We first describe the nature of reform in New Zealand, and then we develop a qualitative model of the adjustment processes set in motion by deregulation. The process of strategic adaptation is represented as a continuum comprising four stages: stability, survival, sharpbending and sustained adaptation. This model is embellished with evidence on actual changes that have been observed in New Zealand business since deregulation. We conclude that, after eight years of substantial economic reform, the majority of businesses have not fully adapted to the new environment.